TEM analysis and determination of dislocation densities in nanostructured copper tube produced via parallel tubular channel angular pressing process - Faraji, G.; Mashhadi, M.M.; Bushroa, Abdul Razak; Babaei, A. (Elsevier, 2013)
Parallel tubular channel angular pressing (PTCAP) is a recently developed novel intense plastic deformation method appropriate for fabrication ultrafine-grained and nanostructured cylindrical tubes. In the present work a commercially pure copper was processed via multi-pass PTCAP and the effects of number of passes on grain refinement and the dislocation density were studied. TEM analysis showed that after first pass elongated subgrains with interior tangled dislocations were formed. After pass number two the density of interior dislocations through the elongated grains was decreased. In the next stages of deformation, at pass number three, elongated grains almost disappeared and equiaxed grains with grain size about 150 nm are formed as a result of dynamic recovery. The dislocation densities were measured by hardness indentation size effect using the Nix–Gao model. The results showed that increase in the number of PTCAP passes leads to decrease in the dislocation densities. The dislocation density is decreased to 2.48×109 cm−2 after fourth passes from 18.1×109 cm−2 after first pass. TEM results verified calculated values from the Nix–Gao model. Microhardness of the PTCAP processed tube through four passes increased to ∼142 HV from initial value of about 62 HV. Also, significant increase takes place after single pass and in the next passes the hardness value is saturated.